Submolecular Ligand Size and Spacing for Cell Adhesion (Adv. Mater. 27/2022). Issue 27 (7th July 2022) - Kim, Yuri; Koo, Thomas Myeongseok; Thangam, Ramar; Kim, Myeong Soo; Jang, Woo Young; Kang, Nayeon; Min, Sunhong; Kim, Seong Yeol; Yang, Letao; Hong, Hyunsik; Jung, Hee Joon; Koh, Eui Kwan; et al.
Abstract : Cell Adhesion In article number 2110340, Ramasamy Paulmurugan, Young Keun Kim, Heemin Kang, and co‐workers report template‐mediated in situ tuning of nanoligand size and spacing. They demonstrate that submolecular ligand spacing and magnetic ligand anchoring facilitate adhesion‐structure assembly‐mediated pro‐healing polarization of host macrophages. Increasing the ligand spacing significantly suppresses macrophage adhesion whereas increasing both ligand size and spacing slightly inhibits it.